Integrasi Teori Belajar Sosial dalam Pembelajaran Pendidikan Agama Islam di Era Digital - Rishan, Muhamad; Batubara, Juliana; Deliani, Nurfarida (TSAQOFAH, 2024)
The integration of social learning theory in Islamic Religious Education (PAI) learning is a relevant approach to face the challenges of the digital era. This article discusses the application of social learning theory, developed by Albert Bandura, in supporting innovative and adaptive Islamic Education learning. This theory emphasizes the importance of observation, modeling, reinforcement, and self-efficacy in learning. By utilizing digital technology, such as learning videos, simulations, and social media, Islamic values can be taught in a more interactive, interesting, and relevant to students' lives. This research uses a descriptive qualitative approach based on literature study, with Miles and Huberman data analysis, namely by analyzing various relevant sources. The results show that the use of technology in Islamic education learning, such as Islamic game-based applications, worship simulation videos, and social media platforms, allows students to understand religious values through real and contextual experiences. The integration of social learning theory helps build a strong connection between Islamic Religious Education learning and students' digital lives. The technology also plays a role in strengthening students' self-efficacy, increasing motivation, and rewarding positive behavior through digital reinforcement mechanisms.